The salivary glands of Brontocoris tabidus (Heteroptera: Pentatomidae): Morphology and secretory cycle. (June 2021) - Carvalho, Paulo Eduardo Gomes Rodrigues; Martínez, Luis Carlos; Cossolin, Jamile Fernanda Silva; Plata-Rueda, Angelica; Viteri Jumbo, Luis Oswaldo; Fiaz, Muhammad; Carvalho, Acácio Geraldo; Zanuncio, José Cola; Serrão, José Eduardo
Highlights: The salivary gland of a predatory insect is described according to feeding status. Fed and starved insects have different feature in the salivary gland cells. Data on morphology of salivary glands indicate that the predator can feed constantly. Abstract: Brontocoris tabidus (Signoret) (Heteroptera: Pentatomidae) is a zoophytophagous insect used for biological control in agriculture and forest systems because its nymphs and adults feed on insects and plants. The predatory Pentatomidae insert the mouthparts into the prey, releasing saliva to paralysis and kills the insect, as well as digest body parts to be sucked in a preliminary extra-oral digestion. In a short period of time, this insect shows the ability to feed again, suggesting the existence of a constant and abundant secretory cycle in the salivary glands. This study evaluated the morphological, histochemical and ultrastructural changes of the salivary glands of B. tabidus in fed and starved insects. The salivary complex of this predatory bug has a pair of bilobed salivary glands and a pair of tubular accessory salivary glands. The accessory glands have the lumen lined by a thick non-cuticular layer rich in glycoproteins. The secretory cells of the B. tabidus principal salivary glands have constant secretory activity, with each lobe producing different substances. The physiological processes that occur in the salivary gland of B. tabidus indicate that the insect needs to feed constantly, corroborating the potential of this insect to be used in biological control programs.